2019
DOI: 10.21273/hortsci13875-19
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging Tolerance of 57 Plant Species Grown Hydroponically

Abstract: Plans for hydroponic experiments, as well as the flooding of watersheds for ecological restoration, require abundant evaluation information regarding plant species adapted to waterlogged environments. In this study, we observed the growth rate and phenotypes of 57 plant species, including nine provenances of four species grown hydroponically. The 57 species were from 22 families and 33 genera, and their waterlogging tolerance (WT) was classified into five categories according to the results of the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Indeed, Cleistocalyx operculatus and S. jambos belong to the Myrtaceae family. They are evergreen medicinal woody plants with waterlogging tolerance and often used in the restoration and reconstruction of riparian zones of tropical and subtropical regions (Jing et al, 2001;Sharma et al, 2013;Nguyen et al, 2017;Ma et al, 2019). In the present study, the pure and mixed planting patterns of C. operculatus and S. jambos under well-watered condition and waterlogging stress were designed and used in answering the following questions: (1) Can these two species benefit from the mixed planting pattern under wellwatered conditions?…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Cleistocalyx operculatus and S. jambos belong to the Myrtaceae family. They are evergreen medicinal woody plants with waterlogging tolerance and often used in the restoration and reconstruction of riparian zones of tropical and subtropical regions (Jing et al, 2001;Sharma et al, 2013;Nguyen et al, 2017;Ma et al, 2019). In the present study, the pure and mixed planting patterns of C. operculatus and S. jambos under well-watered condition and waterlogging stress were designed and used in answering the following questions: (1) Can these two species benefit from the mixed planting pattern under wellwatered conditions?…”
Section: Introductionmentioning
confidence: 99%
“…However, no study has focused on its metabolome profile under stress, and little is known about its molecular stress tolerance. A recent study has suggested that D. odorifera is an excellent tree to use in wetlands [38]. A recent article acknowledged how varying stress levels affect plant metabolism and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Six woody plant species involving D . odorifera have been suggested to be suitable for the ecological restoration of flooded watershed areas (Ma et al, 2019). D. odorifera exhibited new leaf growth and high fresh biomass growth rate under long-term hydro-culture.…”
Section: Introductionmentioning
confidence: 99%